Anencephaly: Case report and literature review - Kamal El Moussaoui; Sara El Bakkali; Ibrahim Ghrab; Aziz Baidada; Aicha Kharbach (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2021)
Anencephaly is a lethal fetal neurological malformation. This malformation accounts for 40% of neural tube malformations. The diagnosis is based on the ultrasound of the 1st trimester between the 11th and the 14th weeks of amenorrhea by the discovery of an exencephaly which results in the visualization of the ossification of the cranial box and therefore of the impossibility to measure the biparietaldiameter. The objective of our work is to highlight the importance of an early ultrasonic diagnosis of anencephaly, which could help in a thorough evaluation and active management. Also, the main role of folic acid in the prevention in neural tube defects.